Composted sewage sludge in replacement of mineral fertilization on wheat production and development - Kummer, Ana C.B. (2016)
Several research lines are required to ensure a proper disposal of sewage sludge in Brazil; among them, we may highlight agricultural use. In this sense, this study aimed at assessing the effect of exchanging nitrogen sourcing via conventional fertilization (chemical) with growing doses of composted sewage sludge (CSS) on wheat crop performance. The experiment was performed in a completely randomized design with seven treatments and ten replications, being defined as T0 (control - without fertilization); T1 (100% mineral fertilization); T2 (50% mineral + 50% CSS); T3, T4, T5, and T6 (100, 150, 200, and 250% nitrogen fertilizing from CSS). Results showed that the use of CSS increased wheat production and development, therefore enhancing its performance. Thus, exchanging mineral fertilization with CSS application raised wheat yields.